(untitled) (Revista de Artes Marciales Asiáticas, 2012)
A number of statements in the gospels of the New Testament describe the behavior of Jesus-bar-Joseph of Nazareth in Galilee in a way that suggests that he may have been acquainted with certain martial arts techniques. We examine these statements in some detail and then proceed to consider what martial arts traditions may have been extant in south-western Asia, more specifically in Palestine, in the first century CE.